Structural, Electrical, and Ethanol-Sensing Properties of La1-xNdxFeO3 Nanoparticles - Nguyen Thi Thuy; Dang Le Minh; Ho Truong Giang; Nguyen Ngoc Toan (Advances in Materials Science and Engineering)
The nanocrystalline La1-xNdxFeO3 (0≤x ≤1.0) powders with orthorhombic perovskite phase were prepared by sol-gel method. The average crystallite sizes of La1-xNdxFeO3 powders are about 20 nm. The resistance and gas-sensing properties of the La1-xNdxFeO3 based sensors were investigated in the temperature range from 160 to 300°C. The results demonstrated that the resistance and response of the perovskite thick films changed with the increase of Nd content.